THE CONTROL SYSTEMS AT SIGNAL CONTROLLED JUNCTIONS FOR BUS PRIORITY - Kupculjakova, Jana (Doprava a spoje, 2012)
The article deals with the issue of urban public transport priority at signal controlled junction where the most time losses are achieved. The way which is possible to ensure the increasing of the efficiency of use of existing roads in the cities is the building a system of public transport priority. A variety of traffic signal control systems and associated strategies are operational in different cities around the world. These may be conveniently grouped into the two categories - isolated systems, such as MOVA, and co-ordinated systems - SCOOT, SCATS, MOTION, UTOPIA/SPOT